(untitled) (Politeja, 2020)
This article aims to determine current political identity of the U.S. Supreme Court by analyzing the process of appointment of its recent Justices and their ideology. The Author claims that ideology and politics play decisive role on Court’s jurisprudence, but that it was Anthony Kennedy’s retirement in 2018 which defined the direction of Court’s adjudication for years to come. The analysis shows important role of the President and Senate in the process of indirect interpretation of the Constitution by the appointment of Justices representing certain ideology.